2022
DOI: 10.3390/membranes12020225
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Preconditioned Extracellular Vesicles from Mesenchymal Stem Cells Improve Cartilage Repair in Osteoarthritis

Abstract: In the past decade, mesenchymal stem cells (MSCs) have been widely used for the treatment of osteoarthritis (OA), and extracellular vesicles (EVs) may play a major role in the efficacy of this treatment. Hypoxia can change the cargo and biological functions of MSC-derived EVs (MSC-EVs). The aim of the present study was to determine whether the effects of hypoxia-preconditioned MSC-EVs on OA cartilage repair are superior to normoxia-preconditioned MSC-EVs. By using in vitro and in vivo OA models, we verified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…Thus, in vivo assays have shown that an injectable silk-fibroin hydrogel, containing articular chondrocytes and MSC-derived EV in hypoxia promoted cartilage regeneration[ 120 ]. Several miRNA were involved in this process, including miR-18a-3p, miR-181c-5p, miR-205-5p, miR-337-5p, and miR-376a-5p[ 120 , 121 ].…”
Section: Therapeutic Potential Of Ev Derived From Msc Preconditioned ...mentioning
confidence: 99%
“…Thus, in vivo assays have shown that an injectable silk-fibroin hydrogel, containing articular chondrocytes and MSC-derived EV in hypoxia promoted cartilage regeneration[ 120 ]. Several miRNA were involved in this process, including miR-18a-3p, miR-181c-5p, miR-205-5p, miR-337-5p, and miR-376a-5p[ 120 , 121 ].…”
Section: Therapeutic Potential Of Ev Derived From Msc Preconditioned ...mentioning
confidence: 99%
“…Next, we compared our results with other works that evaluated the miRNA content of N- and H-EVs [ 59 , 60 , 61 ]. It is noteworthy that the analyzed studies used different cells to produce the EVs and had differences in the methodologies and parameters of analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Culture-expanded MSCs may exert a therapeutic effect through immune modulation and via trophic actions on local joint cells through secreted factors without directly participating in new cartilage formation ( Mak et al, 2016 ; Zhang et al, 2022 ). Consequently, non-cellular biologically-based strategies harnessing the MSC secretome have been explored for cartilage and bone repair ( Kalluri and LeBleu, 2020 ; To et al, 2020 ; Zhang et al, 2022 ).…”
Section: Cell-based Therapies For Osteoarthritismentioning
confidence: 99%
“…Culture-expanded MSCs may exert a therapeutic effect through immune modulation and via trophic actions on local joint cells through secreted factors without directly participating in new cartilage formation ( Mak et al, 2016 ; Zhang et al, 2022 ). Consequently, non-cellular biologically-based strategies harnessing the MSC secretome have been explored for cartilage and bone repair ( Kalluri and LeBleu, 2020 ; To et al, 2020 ; Zhang et al, 2022 ). MSC-derived extracellular vesicles (MSC-EVs) are MSC-produced nanovesicles ranging from 10 nm to several μm in diameter that contain components such as messenger RNA, microRNA, lipids, and bioactive proteins that produce regenerative paracrine effects within damaged tissue ( To et al, 2020 ).…”
Section: Cell-based Therapies For Osteoarthritismentioning
confidence: 99%